Reliability and Validity of a Medicine Ball–Contained Accelerometer for Measuring Upper-Body Neuromuscular Performance. Issue 7 (July 2018) - Roe, Gregory; Shaw, William; Darrall-Jones, Joshua; Phibbs, Padraic J.; Read, Dale; Weakley, Jonathon J.; Till, Kevin; Jones, Ben
Abstract : Abstract: Roe, G, Shaw, W, Darrall-Jones, J, Phibbs, PJ, Read, D, Weakley, JJ, Till, K, and Jones, B. Reliability and validity of a medicine ball–contained accelerometer for measuring upper-body neuromuscular performance. J Strength Cond Res 32(7): 1915–1918, 2018—The aim of the study was to assess the between-day reliability and validity of a medicine ball–contained accelerometer (MBA) for assessing upper-body neuromuscular performance during a throwing task. Ten professional rugby union players partook in the study. Between-day reliability was assessed from the best score attained during 2 sets of 3 throws, on 2 testing occasions separated by 7 days. Validity was assessed against a criterion measure (Optioelectronic system) during 75 throws from a subgroup of 3 participants. The MBA exhibited a small between-day error of 2.2% (90% confidence intervals; 2.0–4.6%) and an almost perfect relationship with a criterion measure ( r = 0.91 [90% CIs; 0.87–0.94]). However, the mean bias and standard error were moderate (7.9% [90% CIs; 6.6–9.2%] and 4.9% [90% CIs; 4.2–5.7%], respectively). Practitioners using an MBA to assess neuromuscular performance of the upper body must take into account the overestimation and error associated with such assessment with respect to a criterion measure. However, as the error associated with between-day testing was small and testing is easy to implement in applied practice, an MBA may provide a useful tool for monitoring upper-body neuromuscular performance over time.